A brief review on technological evolution of vascular microcatheter design. (2021) - Dey, Suman; Mishra, Ruby; Mohapatra, Manoranjan
Abstract: Technological advances have revolutionized the healthcare in the last few decades. Recent methods of treatment focus on minimal invasive techniques like laparoscopic or robotic assisted surgery etc. Endovascular treatment is one such minimal invasive method carried inside blood vessel using small flexible tubes called microcatheter. Many types of procedures like opening of a blocked artery (angioplasty) blocking a bleeding artery (embolization), treating abnormally developed blood vessel (AVM) is carried out using microcatheter. To meet these various needs, the micro catheter's design has been modified from a simple tube to complex structure. The ideal microcatheter should be strong, flexible, trackable and steerable. The existing design is not able meet all the characteristics. Recently emphasis is given on catheter design for better maneuverability. Indigenous research and improvised designs are contemplated by some great minds working unanimously around the world. The review deals with the implementation of micro sensing devices to control the bending characteristics in the microcatheter for an efficacious passage in the tortuous vasculature. Actuators like-polymer conducting layers, pressure sensors, CMOS circuits etc. are used to perceive an exceptional control method for precise bending of the layers. Artificial Intelligence (AI) and deep learning techniques are some potential techniques that can be used for optimized results and accurate control methods.